Edukasi Gizi Seimbang untuk Pencegahan Stunting pada Anak Prasekolah di Wilayah Kerja Puskesmas Dungingis - Evie, Sova; Azwar, Azwar; Ra'bung, Alfrida Semuel; Hasni, Hasni; Saman, Saman; Suswinarto, Dwi Yogyo (Poltekita: Jurnal Pengabdian Masyarakat, 2024)
During its progression, a stunted kid will have challenges with cognitive development and educational failure, which slows down the child's capacity to absorb knowledge and, eventually, leads to low productivity as an adult. The nutritional health of pre-school children should be carefully monitored since this era is crucial as it sets the stage for a child's future growth. Educating parents of preschool-aged children on the need of a healthy diet in warding off stunting is the overarching goal of this community service (Pengabmas) project. Lectures, Q&A sessions, and group discussions were the means of instruction for this task. Fifty participants from the working area of the Dungingis Health Center in Tolitoli Regency who are parents of preschool-aged children will be the focus of this program. Knowledge increased from 38% to 85% according to the findings of the post-test that was administered. Parents' understanding of the need of a healthy diet for pre-schoolers has grown as a result of this educational activity. The goal of the nutrition program at the Dungingis Community Health Center is to help parents better understand how to meet their pre-school children's nutritional needs by educating them about balanced nutrition at least once every three months.